New insights in application of mesenchymal stem cells therapy in tumor microenvironment: pros and cons - Afkhami, Hamed; Mahmoudvand, Golnaz; Fakouri, Arshia; Shadab, Alireza; Mahjoor, Mohamad; Komeili Movahhed, Tahereh (Frontiers in Cell and Developmental Biology, 2023)
Multipotent mesenchymal stem cells (MSCs) are widely accepted as a useful tool for cell-based therapy of various diseases including malignancies. The therapeutic effects of MSCs are mainly attributed to their immunomodulatory and immunosuppressive properties. Despite the promising outcomes of MSCs in cancer therapy, a growing body of evidence implies that MSCs also show tumorigenic properties in the tumor microenvironment (TME), which might lead to tumor induction and progression. Owing to the broad-spectrum applications of MSCs, this challenge needs to be tackled so that they can be safely utilized in clinical practice. Herein, we review the diverse activities of MSCs in TME and highlight the potential methods to convert their protumorigenic characteristics into onco-suppressive effects.